Peningkatan pengetahuan tentang hipertensi untuk menyetabilkan tekanan darah pada keluarga - Andiri Zharfa Asmarani; Desry; Dina Mega Tresna Pamungkas; Elza Dwi Zuvita; Elsha Aulia Mustika (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2021)
Introduction:Hypertension is a disease where a person's condition is when his blood pressure is above 140/90 mmHg. Hypertension is still one of the big enough problems in health to still be overcome. This disease can lead to the emergence of various more severe diseases, such as stroke, kidney disease, heart failure and can also cause death over time. Objektive: The purpose of this counseling is to educate about the problem of hypertension. Because there are still some people who do not understand hypertension. Method: The method he uses is holding a question and answer session given to the family at the end of the counseling evaluation. This is in order to increase basic knowledge about hypertension and can also apply it to daily life as given. The counseling is divided into several parts, namely timeliness and duration, participation, and solving problems. Result: The results of the activity show that it has been carried out well in accordance with the results indicators and criteria on the observation sheet instrument. However, there are some that do not match the results criteria. There are five kinds of research sheets, namely timeliness and duration, participation, knowledge, and problem solving. Conclusion: The evaluation showed that giving responses to the questions given, could answer the questions correctly, but after health education gave the correct feedback. This shows that the status of knowledge changes before and after health education is carried out. Suggestions for this activity need time management so that counseling can be carried out according to the time specified in SAP.